2012
DOI: 10.1111/j.1365-2966.2012.20568.x
|View full text |Cite
|
Sign up to set email alerts
|

The stability of the suggested planet in the ν Octantis system: a numerical and statistical study

Abstract: We provide a detailed theoretical study aimed at the observational finding about the ν Octantis binary system that indicates the possible existence of a Jupiter‐type planet in this system. If a prograde planetary orbit is assumed, it has earlier been argued that the planet, if existing, should be located outside the zone of orbital stability. However, a previous study by Eberle & Cuntz concludes that the planet is most likely stable if assumed to be in a retrograde orbit with respect to the secondary system co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Smooth, coloured curves are for formal 1,2,3σ levels of the best-fit model marked with a star symbol. ously, we found stable solutions only as retrograde orbits, actually in accord with the original hypothesis in (Eberle & Cuntz 2010) and later investigated by Quarles et al (2012). This is illustrated in Fig.…”
Section: Newtonian Model With Stability Constraintssupporting
confidence: 89%
See 1 more Smart Citation
“…Smooth, coloured curves are for formal 1,2,3σ levels of the best-fit model marked with a star symbol. ously, we found stable solutions only as retrograde orbits, actually in accord with the original hypothesis in (Eberle & Cuntz 2010) and later investigated by Quarles et al (2012). This is illustrated in Fig.…”
Section: Newtonian Model With Stability Constraintssupporting
confidence: 89%
“…Earlier, Eberle & Cuntz (2010) following the stability studies of the restricted three body problem by Jefferys (1974) found that a retrograde orbit of the planet lies in much wider stable zone than the direct configuration. In a new work, Quarles et al (2012) investigate this model, extending the set of orbital configurations, through a numerical study in the framework of the elliptic, restricted three-body problem.…”
Section: Introductionmentioning
confidence: 99%
“…The controversial geometry of ν Oct has been investigated with increasing depth beginning with Eberle & Cuntz (2010) and subsequently by Quarles, Cuntz & Musielak (2012) and Goździewski et al (2013). Goździewski et al explored the system in considerable detail and found that stable solutions consistent with the Ramm et al results existed but were confined to tiny regions of the phase space.…”
Section: Introductionmentioning
confidence: 89%
“…This posed a problem for the confirmation of the exoplanet. However, if one considers an exoplanet in retrograde orbit relative to the orbiting binary, then enlarged regions of stability arise, which would be consistent with the putative exoplanet [Eberle and Cuntz, 2010b, Quarles et al, 2012a, Goździewski et al, 2013. The restricted three-body problem has also been applied to P-type or circumbinary exoplanets.…”
Section: Binary Stellar Systems With a Giant Or Terrestrial Exoplanetmentioning
confidence: 99%